Selection of main mechanical ventilators for underground coal mines : a case study - Jha, Ajay Kumar (Springer, 2017)
This book provides information on proper underground mine ventilation in order to detail its importance in maintaining safe, productive, healthy and effective underground environments at all times for employees. The text covers correct design, implementation and maintenance of mine ventilation through suitable fan installation, and keeps in mind the economic requirements of undertaking safe procedures and implementations to ensure that ventilation is optimal. Through three main goals, the book addresses the need for proper fan ventilation in the potentially hazardous conditions of an underground mine. The first goal is to summarize and update the technical information on the strategic importance of selecting suitable techno-commercial main mechanical ventilators for a coal mine. The second goal is to provide a user friendly computer program to help any practicing engineers, mine operators, regulators and researchers in choosing the main mechanical ventilators. Factors in this selection process include environmental requirements, regulatory conditions, occupational health related issues, and cost. The third goal is to provide applications for computer programs meant to determine proper selection and implementation of the main mechanical ventilators. The text is geared towards teachers, researchers, policy makers, environmental organizations and mine operators who wish to teach about or implement the best possible ventilation systems for the health and safety of mine workers.
Keywords: Mine ventilation -- Equipment and supplies -- Case studies.; Coal mines and mining -- Equipment and supplies -- Case studies.; elektronické knihy; electronic books